2022
DOI: 10.2147/dddt.s393122
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide Attenuates Skin Lesions and Inflammation in Rosacea-Like Mice Induced by Long-Term Exposure of LL-37

Abstract: Purpose Most of the existing studies focus on the early inflammation of rosacea, with few interventions on the later development of fibrosis and the relationship between thalidomide and rosacea. The purpose of this study was to construct a long-term induction model and explore the effects of thalidomide on the later stage of inflammation and early stage of fibrosis in rosacea. Patients and Methods BALB/c male mice were randomly divided into four groups: control group, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The morphology, Western blotting, and immunofluorescence results jointly showed that the rosacea-like skin lesions induced by long-term LL-37 administration exhibited simultaneous thickening of the epidermis and dermis with a high degree of collagen hyperplasia and deposition. This outcome differed from the presentation of rosacea-like lesions induced by short-term LL-37 administration [ 32 ] but was similar to what we have seen in previous studies employing intradermal injections of LL-37 every 24 h for 20 days [ 33 ]. In addition, in studies on bleomycin-induced skin fibrosis, collagen deposition was found to be accompanied by the thickening of both the dermis and epidermis, as well as the upregulation of α-smooth muscle actin and wave protein expression levels [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 84%
“…The morphology, Western blotting, and immunofluorescence results jointly showed that the rosacea-like skin lesions induced by long-term LL-37 administration exhibited simultaneous thickening of the epidermis and dermis with a high degree of collagen hyperplasia and deposition. This outcome differed from the presentation of rosacea-like lesions induced by short-term LL-37 administration [ 32 ] but was similar to what we have seen in previous studies employing intradermal injections of LL-37 every 24 h for 20 days [ 33 ]. In addition, in studies on bleomycin-induced skin fibrosis, collagen deposition was found to be accompanied by the thickening of both the dermis and epidermis, as well as the upregulation of α-smooth muscle actin and wave protein expression levels [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 84%
“…The drug functions by inhibiting the Ca 2+ -CaMKII-dependent mTOR-NF-kβ signaling pathway ( 97 ). Continuing the theme of LL-37 modulation for treatment of rosacea, thalidomide has been shown to alleviate rosacea phenotypes in a mouse model by reducing the production of cytokines and chemokines induced through LL-37 ( 98 , 99 ). Another medication with therapeutic potential around the cathelicidin pathway is supramolecular salicylic acid (SSA).…”
Section: Future Therapies and Rational Targetsmentioning
confidence: 99%
“…Silicosis is a common form of pulmonary fibrosis in China (Li et al 2022b ) 39 Thalidomide derivative CC-885 was found to be a Basonuclin 2 (BNC2) inhibitor. The transcript BCN2 is responsible for simulating fibrosis signalling in tissues (Bobowski-Gerard et al 2022 ) 40 Thalidomide effectively lowered skin lesions, inflammation and fibrosis related factors in rosacea mice model (Kang et al 2022 ) …”
Section: Introductionmentioning
confidence: 99%